The Analysis of QRIS Usage and Its Impact on the Velocity of Money in Indonesia - Fadhil, Muhammad; Dawood, Taufiq C.; Seftarita, Chenny (Graha Primera Saintifika, 2025)
QRIS, or Quick Response Code Indonesian Standard, represents one of the key evolutions in the payment system in Indonesia, utilizing QR Code technology to enhance payment system efficiency. QRIS has gained popularity in supporting payment systems in Indonesia and ensuring the velocity of money within the country. The velocity of money plays an important role in enhancing the effectiveness of monetary policy through its influence on the predictability of major monetary aggregates and money demand. This study aims to analyze the impact of QRIS usage on the velocity of money in Indonesia. The study employs a quantitative approach, using quarterly time series data (2019 Q1 - 2023 Q4) and incorporating several additional variables that can influence the velocity of money. The findings indicate that QRIS affects the velocity of money in the long term, as demonstrated through the Error Correction Model, a method capable of analyzing both short-term and long-term economic phenomena and evaluating the consistency of empirical models with economic theory. Based on these empirical results, it is recommended that the government of Indonesia enhance QRIS infrastructure to foster greater confidence and trust among citizens, thereby accelerating transactions.